Multiplexed Immunohistochemistry and Digital Pathology as the Foundation for Next-Generation Pathology in Melanoma: Methodological Comparison and Future Clinical Applications - Van Herck, Yannick; Antoranz, Asier; Andhari, Madhavi Dipak; Milli, Giorgia; Bechter, Oliver; De Smet, Frederik; Bosisio, Francesca Maria (Frontiers in Oncology, 2021)
The state of the art for melanoma treatment has recently witnessed an enormous revolution, going from a chemotherapeutic approach in which one drug was used for all patients to a molecular- and immunological-based approach that has the potential to bring us closer to personalized therapy. Nevertheless, there is still a large margin for improvement in the methods used to characterize all the tumoral features unique to each patient. While the clinical introduction of next generation sequencing has made it possible to perform a deep mutational profiling and match targeted therapies, improving response rates to immunotherapy also requires a deeper understanding of the immune microenvironment and the specific contribution of each component in a patient-matched way. Recent advancements in artificial intelligence and single-cell profiling of resected tumor samples have the potential to pave the way for this challenging task. In this review, we will provide an overview of the state-of-the-art and the potential use of artificial intelligence and multiplexed immunohistochemistry in pathology for the improvement of melanoma diagnosis and treatment. A major asset of in-situ single cell profiling methods is that these preserve the spatial distribution of the cells in the tissue, allowing researchers to not only determine the cellular composition of the tumoral microenvironment, but also study tissue sociology, making inferences about specific cell-cell interactions and visualizing distinctive cellular architectures that have an impact on anti-tumoral response rates. Despite the many advantages, the introduction of these approaches requires the digitization of tissue slides which poses substantial challenges that need to be addressed before these can enter clinical routine.